Cash and profit efficient in Malaysia and South Korea listed company using non-parametric DEA method and parametric regression method - Soh, Wei Ni; Md Nassir, Annuar; Cheng, Fan Fah (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
A corporate cash holding is significant element in the cash and liquidity management. Corporations with higher excessive cash reserves will benefit when high liquidity makes it easier for managers to transfer funds among several of the corporations’ expenses and debts, and allows for more flexibility in managing daily operational activities. However, it raise some issue as firm with higher cash holdings tend to explore to higher agency cost due to the conflict of interest between ownership and management. This study employs data envelopment analysis (DEA) estimation and two-stage regressions model. The findings conclude that the firm size, firm growth, and gross domestic product (GDP) are statistically significant for firm efficiency in both markets. The cash holdings help improve firm efficiency as the adjusted R-square is significantly increased for all models. However, the cash holdings are not related to the efficiency of high-cash holding firms for these two stock exchanges. The contribution of cash holdings to firm efficiency is higher, and even double for a developed market compared with a developing market (Bursa Malaysia), which shows that the development stage of a country impacts on cash holdings’ contribution to firm efficiency.